2017
DOI: 10.1007/s00508-017-1173-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of caveolin-1 in breast cancer stroma as a potential prognostic biomarker of survival and progression: a meta-analysis

Abstract: Our results indicated that lack of expression of caveolin-1 in the breast cancer stroma is associated with a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…Given this, it is possible that the differences are due to histological subtype if the cohort in the Onion study was mainly composed of cases of squamous NSCLC. Loss of Cav-1 has previously been shown to correlate with poor survival in other cancers, for example prostate 83 and breast 84 , in agreement with the Onion study but given the discrepancies identified in this analysis, further studies assessing the prognostic role of Cav-1 in CAFs in NSCLC would be warranted to clarify its prognostic role in lung cancer.…”
Section: Cellular Procceses In Cafssupporting
confidence: 87%
“…Given this, it is possible that the differences are due to histological subtype if the cohort in the Onion study was mainly composed of cases of squamous NSCLC. Loss of Cav-1 has previously been shown to correlate with poor survival in other cancers, for example prostate 83 and breast 84 , in agreement with the Onion study but given the discrepancies identified in this analysis, further studies assessing the prognostic role of Cav-1 in CAFs in NSCLC would be warranted to clarify its prognostic role in lung cancer.…”
Section: Cellular Procceses In Cafssupporting
confidence: 87%
“…These results suggest that Cav-1 might play a different biological role, depending on its compartmentalization. This differential effect has been confirmed in other studies, even if its prognostic value is not clear-cut (12,13,18). What appears to be the most interesting aspect, from the point of view of practical implications, is the predictive value of the Cav-1 IHC signature referred to the efficacy of weekly nab-paclitaxel and gemcitabine, as these results suggest that it may be possible to identify distinct mBC phenotypes that are characterized by different sensitivity to treatment (6).…”
mentioning
confidence: 55%
“…Cav-1 is an integral component of plasma membranes that forms the major structural constituent of caveolae (flask-shaped invaginations of plasma membrane), which are found at the cell surface in most cell types (12). Increasing amount of data shows that Cav-1 is expressed in many mesenchymal cells, such as adipocytes, fibroblasts and endothelial cells (13). The "genesis" of human cancer, ultimately due to genomic instability, encompasses a broad spectrum of different processes.…”
mentioning
confidence: 99%
“…However, Cav1 -dysregulated cells appear “predisposed” to display aberrant signaling profiles given proper stimuli [ 10 , 11 , 13 15 , 20 22 ]. This predisposition, or reprogramming, suggests CAV1 as a facilitator of immune/inflammatory-related processes and could point toward its ultimate role in the progression of multiple human malignancies, including both solid tumor [ 23 25 ] and hematological diseases [ 8 , 26 , 27 ]. To this end, we examined the staining pattern of CAV1 and its expression in follicle-derived B-cell malignancies.…”
Section: Main Textmentioning
confidence: 99%
“…We observed fainter, less stromal-localized CAV1 staining in the hematological malignancies with lower CAV1 expression in tumor biopsies compared to normal splenic tissue. However, no differences were observed between the more aggressive DLBCL cases when compared to the more indolent FL cases, not forming a parallel between lowered CAV1 expression being associated with a more aggressive disease in both breast [ 23 ] and prostate cancer [ 24 ]. These results suggest that CAV1 is dysregulated in follicle-derived B cell malignancies but does not play an overt role between more aggressive and indolent disease entities.…”
Section: Main Textmentioning
confidence: 99%